2012
DOI: 10.4161/cc.11.5.19445
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of Mdm2 C-terminal tail suggests an evolutionarily conserved role of its length in Mdm2 activity toward p53 and indicates structural differences between Mdm2 homodimers and Mdm2/MdmX heterodimers

Abstract: To cite this article: Pavlina Dolezelova, Katerina Cetkovska, Karen H Vousden & Stjepan Uldrijan (2012) Mutational analysis of Mdm2 C-terminal tail suggests an evolutionarily conserved role of its length in Mdm2 activity toward p53 and indicates structural differences between Mdm2 homodimers and Mdm2/MdmX heterodimers, Cell Cycle, 11:5,[953][954][955][956][957][958][959][960][961][962]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 30 publications
5
36
0
Order By: Relevance
“…Consistent with the study mentioned above (27), we showed that ectopically expressed MDM2 with the antiterminating mutation is defective in its ability to degrade both ectopic and endogenous p53 in U2OS cells (Supplemental Figure 2, B and C). In fact, expression of mutant MDM2 led to increased levels of p53 protein in either case.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Consistent with the study mentioned above (27), we showed that ectopically expressed MDM2 with the antiterminating mutation is defective in its ability to degrade both ectopic and endogenous p53 in U2OS cells (Supplemental Figure 2, B and C). In fact, expression of mutant MDM2 led to increased levels of p53 protein in either case.…”
Section: Resultssupporting
confidence: 74%
“…Previous cell-based transfection studies have shown that the highly conserved extreme C-terminus of MDM2 is essential for its oligomerization and E3 ubiquitin ligase activity (25,26). In addition, a more recent study showed that the same MDM2 variant, when ectopically expressed, is unable to degrade coexpressed p53 in vitro (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S9A,B). Consistent with other C ′ -terminal RING domain-containing proteins (Dolezelova et al 2012), there are exactly 13 amino acids following the final cysteine residue, and, as with HDM2 (Fang et al 2000), there are seven critical cysteine residues that are conserved for ubiquitin ligation activity and p53 degradation (Supplemental Fig. S10).…”
Section: Lj-mdm2 and Lj-mdm4 Genesmentioning
confidence: 57%
“…However, recent studies have also implicated the extreme C-terminal amino acids of Mdm2 in E3 ligase function (Uldrijan et al 2007). Mutations of cysteine residues in human MDM2 (C447, C462, or C475) that are critical for the structure of the RING domain (Sharp et al 1999;Argentini et al 2000;Fang et al 2000) or changes in the C-terminal tail length by either deletion of five amino acids or extension of five residues (by bypassing the stop codon) substantially inhibit its E3 ligase activity (Poyurovsky et al 2010;Dolezelova et al 2012). Another important feature of the Mdm2 RING domain is that it interacts with an Mdm2-related protein, Mdm4 (Sharp et al 1999;Tanimura et al 1999).…”
Section: The Mdm2 E3 Ligasementioning
confidence: 99%